1996
DOI: 10.1093/bja/76.1.156
|View full text |Cite
|
Sign up to set email alerts
|

Airway problems after carotid endarterectomy

Abstract: Respiratory obstruction has been reported as a complication of carotid endarterectomy; the causes include traumatic mucosal oedema, direct tracheal compression by haematoma and oedema secondary to lymphatic and venous congestion. We report four cases of acute respiratory obstruction complicating carotid endarterectomy. Two of these cases suffered respiratory arrest in the postoperative ward and required emergency tracheal intubation in difficult circumstances. All of these patients had developed wound haematom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 6 publications
0
14
0
5
Order By: Relevance
“…The authors also suggested that venous congestion may distort the airway and cause obstruction. In evaluating these cases, the possibility of additional factors such as sedation from narcotic administration should be considered, as this may contribute to airway narrowing . This was not, however, considered to play a role in either case presented here.…”
Section: Discussionmentioning
confidence: 92%
“…The authors also suggested that venous congestion may distort the airway and cause obstruction. In evaluating these cases, the possibility of additional factors such as sedation from narcotic administration should be considered, as this may contribute to airway narrowing . This was not, however, considered to play a role in either case presented here.…”
Section: Discussionmentioning
confidence: 92%
“…Laryngospasm is not a possibility after neuromuscular block has been achieved. Consequently, the possibility exists that the patency of this edematous airway [9] depended significantly on intact muscle tone. The airway edema and subsequent airway collapse could explain an airway obstruction distal to the LMA in the clinical scenario described.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid clinical deterioration can occur after stridor develops. 189 Studies by Carmichael and colleagues provided additional evidence for the role of swelling and bleeding in a small but elegant study. They compared the CT scans of 19 patients before and after carotid endarterectomy surgery.…”
Section: Carotid Artery Surgerymentioning
confidence: 99%